2011
DOI: 10.1042/cs20100527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin therapy on cardiac function and survival in a volume-overload model of heart failure in rats

Abstract: The effect of metformin therapy on cardiac function and survival in volume-overload model of heart failure in rats Short title: Metformin therapy in volume-overload heart failure in rats A c c e p t e d M a n u s c r i p t Licenced copy. Copying is not permitted, except with prior permission and as allowed by law.© 2011 The Authors Journal compilation © 2011 Portland Press Limited 2 Abstract Aims: Advanced heart failure (HF) is associated with altered substrate metabolism. Whether modification of substrate use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…Another promising candidate for the promotion of oxidative metabolism could be the antidiabetic drug metformin, that influences the substrate metabolism for OXPHOS by promoting fatty-acid oxidation [136]. Metformin has been reported to increase myocardial palmitate oxidation in a volume-overload rodent model [137] and although the drug did not influence the overall survival of the animals in the study, it might be applied to influence the pathological reprogramming of cardiomyocytes.…”
Section: Mitochondrial Medicine For Heart Diseasesmentioning
confidence: 95%
“…Another promising candidate for the promotion of oxidative metabolism could be the antidiabetic drug metformin, that influences the substrate metabolism for OXPHOS by promoting fatty-acid oxidation [136]. Metformin has been reported to increase myocardial palmitate oxidation in a volume-overload rodent model [137] and although the drug did not influence the overall survival of the animals in the study, it might be applied to influence the pathological reprogramming of cardiomyocytes.…”
Section: Mitochondrial Medicine For Heart Diseasesmentioning
confidence: 95%
“…In a recent study in a model of global heart volume overload caused by aortocaval fistulae (ACF) in rats, metformin was shown to have no impact on the heart and LV weight in ACF rats while echo data showed a trend similar to ours (less dilatation). In that study the dose of metformin was twice the one we used 15 (27). In another study in rats post-myocardial infarction, metformin was shown to decrease heart dilatation while limiting LV wall thinning [28].…”
Section: It Is Not Clear How Metformin (Via Ampk Activation or Not) Cmentioning
confidence: 99%
“…Altered substrate metabolism is associated with advanced heart failure (HF), and metformin is known to affect substrate metabolism leading to improved outcome in diabetic HF. Kazdova et al ( 176 ) examined the effect of metformin on the improvement of cardiac function in nondiabetic volume-overload HF rat model and observed normalization of NEFA and increased palmitate oxidation but no effect on mitochondrial diacylglycerides contributing to insulin resistance ( 143 ). AMPK restores the AMP:ATP ratio through ATP production mediated by increased fatty acid uptake and lipid oxidation ( 113,141,142,144,145 ).…”
Section: Role Of Ampk In Cardiac Functionmentioning
confidence: 99%